Chiasmus of Corporeity and Nature in Ivan Laučík’s Poetry - Fedor Matejov (Slovenska Literatura, 2015)
The present paper dealing with Ivan Laučík´s (1944 – 2004) poetry is organized into several steps. – It was inspired by M. Merleau-Ponty´s ideas about the chiasmus of corporeity and the world, about perceiving elements and things, about the functioning of the living language, fragmentarily known in the Czechoslovak context since the 1960s and probably marginally noticed by I. Laučík. The paper refines cave motifs, or topoi as a synecdoche of nature in Laučík´s poetry – it is done by confronting his own poems with Rudolf Těsnohlídek´s book of documentary essays Demänová published in the year 1926. An attempt at defining the semantics of the motifs is made by referring to Laučík´s essay about speleologist J. Volko-Starohorský, where there are a poetically inspiring designation crisis and a crisis situation of existential corporeal commitment projected into the relation between language and cave experience. The paper highlights as an interpretation problem the transition of Laučík´s poetry from an excessively „open“ way of writing of the late 1960s to relating his poetry of the 1980s to natural and cultural landmarks of the Liptov region, biographically well-know to the poet. These ideas are further exemplified by critical reading of three poems. The poem Jahoda (Strawberry, collection Vzdušnou čiarou, As the crow flies, 1991) shows Laučík´s participation in a latent discussion of the 1980s about ecology, the critical reading documents the biographical context of the poem, notices irony and a commemoration gesture. The poem Alexy´s pastel (from the same collection) moves on from the visual work of art to reviving its model – a sacred architectural monument falling into ruin at that time and shows so far unnoticed possibility or form of Laučík´s poetry – a „quasi-geographical recording of history“ (M. Merleau-Ponty´s formulation). In the case of the poem Milí priatelia! (Dear Friends!, end of the collection Na prahu počuteľnosti, On the Threshold of Audibility, 1988) brief fragmentary critical reading uses the motif of a hat to refine the chiasmus between communication and anonymous loneliness, as well as the motif of avalanche in the sense of liberating risk and disaster. The paper situates Laučík´s poetry, which is difficult to read and sometimes even hermetic, as well as work on it into the perspective predestined by one of the poet´s lines: „...krypty jazyka čakajú na zmŕtvychvstanie...“ („… the tombs of the language await resurrection“).